2006 IEEE International Conference on Industrial Technology 2006
DOI: 10.1109/icit.2006.372243
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Stabilisation in Multi Area System Using HVDC Link

Abstract: When an AC power system is subjected to sudden When an AC power system is subjected to load disturbance, load changes, system frequency will be considerably disturbed the system frequency may be considerably perturbed from the and becomes oscillatory. This is predominant in an operating frequency. The deviation of frequency oscillation interconnected power system. In this paper a new controller is that exceeds the normal limit directly interrupts the operation designed to regulate the tie-line power regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…However, the fundamental frequency may deviate from the nominal value due to various reasons such as disturbances, subsequent transients and or the dramatic real power fluctuations of arc furnace plants as stated in [3][4][5]. In [3], it is reported that the most preferable frequency deviation is ±0.02 Hz, however, for case studies with a large steel mill or an arc furnace plant, the standard change in transient frequency lies between ±0.50 Hz. In [6], it is reported that US-wide power system fre-ଝ This research is carried out through the National Power Quality Project of Turkey.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the fundamental frequency may deviate from the nominal value due to various reasons such as disturbances, subsequent transients and or the dramatic real power fluctuations of arc furnace plants as stated in [3][4][5]. In [3], it is reported that the most preferable frequency deviation is ±0.02 Hz, however, for case studies with a large steel mill or an arc furnace plant, the standard change in transient frequency lies between ±0.50 Hz. In [6], it is reported that US-wide power system fre-ଝ This research is carried out through the National Power Quality Project of Turkey.…”
Section: Introductionmentioning
confidence: 87%
“…: +90 3122101310; fax: +90 3122101315. quency usually varies between 59.99 and 60.02 Hz; however, in case of an event the frequency may drop down to 59.55 Hz. It is observed that during safe operation, the power system frequency deviates due to various reasons; however, in interconnected systems such as the US-power network [6], this deviation is much less than that of the power systems without such an interconnection [3,7]. In FFT-based algorithms, frequency deviation causes leakage effect, which is one of the major problems associated with FFT applications.…”
Section: Introductionmentioning
confidence: 95%
“…In the literature, the control of load frequency of a power network using automatic load frequency control by variation of generation set points on the speed governor to maintain system frequency has been presented in [1, 2]. In a parallel AC–DC interconnected power transmission system [3, 4], the DC system can effectively cooperate with an AC system in improving frequency response. The use of supervisory fuzzy controller to stabilise frequency deviations in an AC–DC interconnected power system was reported in [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several control techniques have been proposed for the LFC of power systems to keep the system parameters at their specified value during sudden and normal loading conditions [1][2][3][4][5][6][7][8][9][10]. Literatures show that the system performance depends on both the employed controller and the selected objective function for tuning the controller parameters.…”
Section: Introductionmentioning
confidence: 99%